Diversification through promotion of export-oriented production and “Green Transformation” in Azerbaijan - Mushfig Guliyev; Tarlan Azizov (Наукові горизонти, 2022)
Diversification is an important component of the development of any economy. The reason for this is the increase in the country's resilience to external stimuli, which makes progress more gradual, constant and predictable. Thus, the study of the possibilities of diversifying the economy is very relevant, especially in today's geopolitical conditions. The purpose of the work was to analyse some methods of diversifying the economy of Azerbaijan, namely the development of export-oriented production and the implementation of the “green transformation”. Analysis became the main method in writing the article, but historical, modelling, deduction, abstract-logical methods also played an important role. Thus, the work examined and analysed the export of Azerbaijan, during which a significant dependence of the country on oil sales to foreign markets was revealed. Since such a prospect is dangerous for the sustainable development of the country, it is important to carry out certain measures aimed at increasing the diversification of its exports. First of all, they are associated with publicprivate partnerships, but they also take other forms, such as attracting investments and building infrastructure. In addition, the paper describes how the “green transformation” of the country can help achieve the goals of economic diversification and at what stage is the level of “greening” of the state economy; the paper also describes the prospects for the state in achieving these goals. The article brings new knowledge to understand the features of the functioning of the Azerbaijani economy, as well as to the theory of economic and sustainable development, as well as trade